2006
DOI: 10.1017/s0043933906001139
|View full text |Cite
|
Sign up to set email alerts
|

Optimal farm size for achieving enterprise objective and sustainability in poultry meat production in Osun State, Nigeria

Abstract: This study attempts to identify the poultry meat farmers' objectives of production, analyse their socio-economic characteristics, determine the optimal farm size and prioritize the constraints to achieving the enterprise objectives. Taking Osun State of Nigeria poultry meat farmers as a case study, data on poultry meat business enterprise objective(s), socio-economic characteristics of farmers and farms, quantity and prices of inputs and output, and constraints to production were collected. Data were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This result is in consonance with Matanmi et al (2012) who reported that the majority of poultry farmers in Kwara State were males. This finding agrees with Alimi et al (2006), who reported that there were more males involved in poultry farming than females. This could be because the male poultry farmers are more positioned and privileged to access capital for establishing their poultry enterprises than their female counterparts.…”
Section: Resultssupporting
confidence: 92%
“…This result is in consonance with Matanmi et al (2012) who reported that the majority of poultry farmers in Kwara State were males. This finding agrees with Alimi et al (2006), who reported that there were more males involved in poultry farming than females. This could be because the male poultry farmers are more positioned and privileged to access capital for establishing their poultry enterprises than their female counterparts.…”
Section: Resultssupporting
confidence: 92%